Defining and Providing Pragmatic Interoperability: The MIDAS Middleware Case - Ribeiro, Elivaldo Lozer Fracalossi; Claro, Daniela Barreiro; Maciel, Rita Suzana Pitangueira (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
Modern information systems are becoming increasingly complex due to the need to combine heterogeneous software. A common understanding of interoperability issues is not a trivial task since complex systems may contain many independent software components. This work presents a Conceptual frAmework for Pragmatic InTeroperAbiLity (CAPITAL) to enhance a pragmatic interoperability unified definition. We evaluate our framework through a modeling and coding guide, a controlled experiment, and applying CAPITAL in the Cloud Computing domain. Results suggest that CAPITAL positively influences the understanding, modeling, and codification of pragmatic interoperability solutions, facilitating pragmatic interoperability standardization opportunities.